Long‐term survival rates of patients undergoing vitrectomy for diabetic retinopathy in an Australian population: a population‐based audit. (20th February 2019) - Liu, Ebony; Estevez, Jose; Kaidonis, Georgia; Hassall, Mark; Phillips, Russell; Raymond, Grant; Saha, Niladri; Wong, George H.C.; Gilhotra, Jagjit; Burdon, Kathryn; Landers, John; Henderson, Tim; et al.
Abstract: Importance: Five‐year survival rates in patients undergoing vitrectomy for diabetic retinopathy (DR) vary from 68% to 95%. No study has been conducted in an Australian population. Background: We aimed to determine the survival rates of patients undergoing diabetic vitrectomy in an Australian population. Design: Retrospective audit, tertiary centre hospitals and private practices. Participants: All individuals in South Australia and the Northern Territory who underwent their first vitrectomy for diabetic complications between January 1, 2007 and December 31, 2011. Methods: An audit of all eligible participants has been completed previously. Survival status as of July 6, 2018 and cause of death were obtained using SA/NT DataLink. Kaplan‐Meier survival curves and multivariate cox‐regressions were used to analyse survival rates and identify risk factors for mortality. Main outcome measures: Five‐, seven‐ and nine‐year survival rates. Results: The 5‐, 7‐ and 9‐year survival rates were 84.4%, 77.9% and 74.7%, respectively. The most common cause of death was cardiovascular disease. Associated with increased mortality independent of age were Indigenous ethnicity (HR = 2.04, 95% confidence interval [CI]: 1.17‐3.57, P = 0.012), chronic renal failure (HR = 1.76, 95% CI: 1.07‐2.89, P = 0.026) and renal failure requiring dialysis (HR = 2.32, 95% CI: 1.25‐4.32, P = 0.008). Conclusions and relevance: Long‐term survival rates after diabetic vitrectomy in Australia are similar to rates reported in other populations. Indigenous ethnicity and chronic renal failure were the most significant factors associated with long‐term mortality. This information can guide allocation of future resources to improve the prognosis of these high risk groups.